MOLECULAR DOCKING STUDIES OF XANTHONE AND CAFFEINE DERIVATIVE COMPOUNDS AS AN ANTICANCER - Sinebar, Wijen
Cancer is the world’s second higest cause of death with an estimated death rate of 9.9 million people in 2020 where lung cancer makes the largest contribution to the number of deaths. The most dominating variant of lung cancer is non-small cell lung cancer (NSCLC) at 80–85%. Epidermal growth factor receptor (EGFR) is a transmembrane tyrosine kinase protein receptor that is often used as a target for lung cancer drug development. The overexpression of EGFR can be inhibited by a small molecule inhibitors such as dacomitinib which is the second generation of EGFR inhibitors. However, dacomitib is known to still cause various unwanted side effects such as diarrhea, dermatological diseases, embryo-fetal toxicity, and pneumonia. Therefore, the search for alternative bioactive compounds, especially those based on natural compounds, is still being pursued. Epoxyquinophomopsin is a quinone derivative compound that isolated from the fungus Phomopsis sp. which host on the branches of Morus cathayana (mulberry). This compound is reported to have a good ability to inhibit EGFR. The compounds tested in this study are xanthone and caffeine derivatives which are known to have antimicrobial bioactivy and induce apoptosis. In this study, molecular docking simulation can be used as an initial screening to see the potential inhibition of the test compounds against EGFR. Molecular docking simulation was done against 6 xanthone-derived compounds and 14 caffeine-derived compounds which were then compared with inhibitors approved by the food and drug administration (FDA) and natural compounds that have been tested for their bioactivity against EGFR. Based on the simulation results, it is known that the compound 60 (1-hidroksi-7-metoksi-2,8- bis (3-metilbut-2-en-1-il)-3,6- bis [4-(pyrrolidin-1-il)butoksi] -9H- xantene-9-one) and compound 73 (N-{ 4 -[( 1,3 -dimetil- 2,6 -diokso- 2,3,6,7 -tetrahidro- 1H- purin-7-il)metil]fenil}-2-(4-metilpiperidine-1-il)asetamida) yielded docking score ?7.4 kcal/mol and ?8.1 kcal/mol, respectively. The interaction analysis showed that the two compounds interacted with residues Lys745 and Cys797 which acts as a catalytic residue also with residue Thr790 which is the gatekeeper of EGFR. This research has succeeded in proving that xanthone and caffeine derivatives have potential as EGFR inhibitors